Additive Manufacturing of Multi‐Scale Porous Soft Tissue Implants That Encourage Vascularization and Tissue Ingrowth. Issue 14 (24th June 2021) - Coulter, Fergal B.; Levey, Ruth E.; Robinson, Scott T.; Dolan, Eimear B.; Deotti, Stefano; Monaghan, Michael; Dockery, Peter; Coulter, Brian S.; Burke, Liam P.; Lowery, Aoife J.; Beatty, Rachel; Paetzold, Ryan; et al.
Abstract: Medical devices, such as silicone‐based prostheses designed for soft tissue implantation, often induce a suboptimal foreign‐body response which results in a hardened avascular fibrotic capsule around the device, often leading to patient discomfort or implant failure. Here, it is proposed that additive manufacturing techniques can be used to deposit durable coatings with multiscale porosity on soft tissue implant surfaces to promote optimal tissue integration. Specifically, the "liquid rope coil effect", is exploited via direct ink writing, to create a controlled macro open‐pore architecture, including over highly curved surfaces, while adapting atomizing spray deposition of a silicone ink to create a microporous texture. The potential to tailor the degree of tissue integration and vascularization using these fabrication techniques is demonstrated through subdermal and submuscular implantation studies in rodent and porcine models respectively, illustrating the implant coating's potential applications in both traditional soft tissue prosthetics and active drug‐eluting devices. Abstract : Porous silicone coatings are additively manufactured onto the surface of soft‐tissue implants, aiming to address the notorious challenges of long‐term tissue integration and fibrosis. The "liquid rope coil effect" via direct ink writing is combined with atomizing spray deposition to create a multi‐scale "rope coiled" silicone coating architecture. In vivo studies show that this coating encourages highly vascularised tissue ingrowth.